Analisis Kemampuan Pemecahan Masalah Peserta Didik Ditinjau dari Kemampuan Matematis Materi PLSV - Siti Asna Rodliyah; Nur Rahmawati; Eni Sari; Mustangin (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to describe student’s problem solving ability in term of mathematical ability in PLSV material. The research method was qualitative research. The subject of this study was 20 of students in grade 7B SMPN 1 Turen that chosen using purposive sampling technique. The Data collection used tests and interviews. The instruments used are a matter of tests and guidelines of interviews. Data analysis is conducted through three stages: data reduction, display data, and verification. The research results show that students with high category abilities has a high mathematical ability to solve the problems by accomplishing all the problem solving ability indicators, students with medium category abilities has a medium mathematical ability to solve the problems but have not accomplished all the problem solving ability indicators yet, and students with low abilities has a low mathematical ability, therefore it has not be able to solve all the problems.